The Role of Ukraine Digital Diplomacy in the Russia-Ukraine Conflict in 2014-2022 - Liyundzira, Aulia; Nugroho, Bambang Wahyu (Journal Research of Social Science, Economics, and Management, 2025)
The Russia-Ukraine conflict is not only taking place on the battlefield, but also developing into a narrative battle in the digital space. Digital diplomacy has become a strategic instrument for Ukraine in shaping international public opinion, mobilizing global support, and countering Russian disinformation during the period 2014–2022. This research aims to analyze the role, strategy, and effectiveness of Ukraine’s digital diplomacy from the annexation of Crimea to the full-scale invasion in 2022. Through a descriptive-qualitative approach, this study examines the digital communication practices of the Ukrainian government, in particular the use of social media by President Volodymyr Zelenskyy, crowdsourced campaigns such as UNITED24, as well as collaborations with global civil networks and the OSINT community. The findings of the study show that Ukraine’s personalized, decentralized, and participatory communication model has succeeded in building international solidarity more effectively than Russia’s strategy that relies on centralized disinformation and bot networks. Ukraine’s digital diplomacy is also capable of converting soft power into significant political, military, and humanitarian support from various countries and international organizations. Thus, digital diplomacy has proven to be Ukraine’s main tool for maintaining legitimacy, strengthening bargaining positions, as well as protecting national interests in asymmetric conflicts with Russia.